Investigating the Effect of COVID-19 on Driver Behavior and Road Safety: A Naturalistic Driving Study in Malaysia - Al-Hussein W.A.; Li W.; Por L.Y.; Ku C.S.; Alredany W.H.D.; Leesri T.; MohamadJawad H.H. (MDPI, 2023)
COVID-19; data acquisition; disease spread; sensor; transportation safety; travel behavior; acceleration; adult; aged; Article; controlled study; coronavirus disease 2019; deceleration; driving ability; female; human; lockdown; Malaysia; male; pandemic; public policy; road safety; speeding (driving); travel restriction; car driving; communicable disease control; epidemiology; traffic accident; Malaysia; Accidents, Traffic; Automobile Driving; Communicable Disease Control; COVID-19; Humans; Malaysia